Workplace accidents in Brazil: analysis of physical and psychosocial stress and health-related factors / Acidentes de trabalho no Brasil: análise do estresse físico, psicossocial e fatores relacionados à saúde - Simarly M. Soares; Simone Gelmini; Silvânia S. S. Brandão; June M. C. Silva (RAM. Revista de Administração Mackenzie, 2018)
Purpose: To identify the influence of physical and psychosocial stress and health-related factors on the occurrence of work-related accidents, based on the National Health Survey (NHS) conducted in Brazil in 2013, through the execution of a retest in the Brazilian context, according to the model elaborated by Rommel, Varnaccia, Lahmann, Kottner, and Kroll (2016). Originality/value: Brazil has a high rate of workplace accidents. This retest, applied to the Brazilian context based on the German model of Rommel et al. (2016), allows obtaining information concerning the factors that may increase the chances of workplace accidents. Design/methodology/approach: Study with secondary data collected from the National Health Survey (Fiocruz, 2013). The model of Rommel et al. (2016)was used with the set of four blocks of variable factors. Logistic regression explored the physical, psychosocial, and health-related stress factors that may be more likely to occur in the workplace. Findings: 2.8% of the individuals have been involved in some work accident. Model 5 is the most explanatory of occupational accidents and factors such as high school level of education (OR = 2.082), full-time work (OR = 4.814), having three or more jobs (OR = 2.593), exposure to radiation, asthma (OR = 4.880), and alcohol consumption (OR = 4.620), according to each block typified, which most significantly increase the chances for the occurrence of work accidents. Managers and legislators should observe the factors that increase the chances of an accident occurring in order to develop prevention policies or actions. Proposta: Identificar a influência do estresse físico, psicossocial e fatores relacionados à saúde para a ocorrência de acidentes de trabalho, tendo como base a Pesquisa Nacional de Saúde (PNS) realizada em 2013 no Brasil, como reteste no contexto brasileiro, conforme o modelo de Rommel et al., (2016). Originalidade/valor: No Brasil há um elevado índice de acidentes de tra balho. Este reteste aplicado ao contexto brasileiro a partir do modelo alemão de Rommel et al. (2016) possibilita apresentar informações em relação aos fatores com maior chance de ocorrência dos acidentes de trabalho. Design/methodologia/abordagem: Estudo com dados secundários cole tados da Pesquisa Nacional de Saúde (Fiocruz, 2013). Foi utilizado o modelo de Rommel et al. (2016) com o conjunto de quatro blocos de fatores de variáveis. A regressão logística explorou os fatores de estresse físico, psicossocial e relacionados à saúde que podem possuir mais chan ces para a ocorrência do acidente de trabalho. Descobertas: 2,8% dos indivíduos se envolveram em algum acidente de trabalho. O modelo 5 é o mais explicativo para os acidentes de trabalho e fatores como ensino médio (OR: 2,082), trabalho em período integral (OR: 4,814), três ou mais trabalhos (OR: 2,593), exposição radioativa (OR: 4,244), asma (OR: 4,880) e, consumo de álcool (OR:4,620) foram identificados como aqueles com maior chance, conforme cada bloco tipi ficado, para a ocorrência do acidente de trabalho. Os gestores e legislado res devem observar os fatores que atribuem mais chances para a ocorrên cia de acidentes para a elaboração de políticas ou ações de prevenção.